Head Injury - A Case Profile Study from Eastern Region of Nepal (Health Renaissance, 2011)
Background: Head injury is a common presentation in emergency rooms. Management often is decided by time of trauma, clinical presentations and availability of facilities. Objective: To outline the general characteristics of head injury patients presenting to emergency. Methods: This is an observational (case series) study done in BPKIHS emergency room over a period of six months. All the acute head trauma cases presenting to the department of emergency, BPKIHS, were evaluated based on the semi closed clinical performa including major clinical indicators of intracranial trauma. Results: Among 255 head injury patients, males were more common. Fall was the commonest mode of injury resulting in 71.42% in those under ten years where as road traffic accidents was commonest in twenty to fifty years age group.23% reached the hospital after 12 hours of injury. Loss of consciousness and vomiting were the commonest history. 9.4% had consumed alcohol at presentation. Mild head injury was commonest (76.5%). 23% were discharged from emergency within 12 hours. 14.9% underwent neurosurgical intervention. 187 of 255 underwent CT scan, 132 were abnormal. Contusions were commonest. For the normal CT scan the mean GCS score was 13.65 and for abnormal CT scans the mean GCS was 12.48 with SD of 2.8 and 3.4 respectively, p=0.025. Keywords: head injury; clinical features; emergency; classification; Glasgow coma score; CT scan. DOI: 10.3126/hren.v8i2.4422 Health Renaissance, May-Aug 2010; Vol 8 (No.2):11--113